2011
DOI: 10.1089/aid.2010.0312
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiological Analysis of Paired pol/env Sequences from Portuguese HIV Type 1 Patients

Abstract: The advent of new therapeutic approaches targeting env and the search for efficient anti-HIV-1 vaccines make it necessary to identify the number of recombinant forms using genomic regions that were previously not frequently sequenced. In this study, we have subtyped paired pol and env sequences from HIV-1 strains infecting 152 patients being clinically followed in Portugal. The percentage of strains in which we found discordant subtypes in pol and env was 25.7%. When the subtype in pol and env was concordant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…15,17 Accordingly, the MHA described in this work (vMHA B/G/02 ) was planned to allow a rapid and unambiguous discrimination of the most prevalent HIV-1 subtypes (subtype B and G) and circulating recombinant forms (CRF02_AG and CRF14_BG) that comprise the majority of the HIV-1 strains circulating in Portugal. [18][19][20][21] In a recent study 28 the same predominant subtypes were found, although an unusually high (and possibly nonrepresentative) prevalence of subtype C was reported. However, the basic features of your method allows for quick updating in the face of a change in distribution of subtypes in Portuguese epidemiology, such as an increased prevalence of a nondominant subtype.…”
Section: Discussionmentioning
confidence: 77%
“…15,17 Accordingly, the MHA described in this work (vMHA B/G/02 ) was planned to allow a rapid and unambiguous discrimination of the most prevalent HIV-1 subtypes (subtype B and G) and circulating recombinant forms (CRF02_AG and CRF14_BG) that comprise the majority of the HIV-1 strains circulating in Portugal. [18][19][20][21] In a recent study 28 the same predominant subtypes were found, although an unusually high (and possibly nonrepresentative) prevalence of subtype C was reported. However, the basic features of your method allows for quick updating in the face of a change in distribution of subtypes in Portuguese epidemiology, such as an increased prevalence of a nondominant subtype.…”
Section: Discussionmentioning
confidence: 77%
“…Since its origin in Africa approximately 100 years ago, HIV-1 has continuously been undergoing genetic diversification that is enhanced by the massive globalization of the human population (21). Despite the perception that current antiretroviral regimens have comparable efficacies across existing diverse HIV-1 subtypes, there is evidence showing that some HIV-1 subtypes may have a transmission advantage, higher replicative efficiency, or even altered drug susceptibility (7)(8)(9)(10)(11), raising awareness on the relevance of investigating HIV-1 diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Existing data show that Portugal contrasts with the rest of western Europe in its distribution of HIV-1 subtypes (18,21). It is important to gain a further understanding on the causes underlying this difference, also in light of the evidence supporting a recent increase in infections with non-B HIV-1 subtypes in several western European countries (15)(16)(17)44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subtype F predominates in Central Africa (Carr et al, 2010b;Soares et al, 2010), South America (Avila et al, 2002;Munerato et al, 2010) and Eastern Europe (Fernandez-Garcia et al, 2009;Paraschiv, Foley, and Otelea, 2011). Subtype G viruses are prevalent in Central and Western Africa (Hawkins et al, 2009;Kalish et al, 2004), as well as in Portugal (Abecasis et al, 2011;Esteves et al, 2003;Esteves et al, 2002;Palma et al, 2007) and Spain Trevino et al, 2011). Subtypes H and J were described in Central Africa Mokili et al, 1999;Yamaguchi et al, 2010) and in Angola (Bartolo et al, 2005;Bartolo et al, 2009d).…”
mentioning
confidence: 99%